Do celebrity endorsement, halal label, and Word of Mouth affect Millennials to purchase skincare? - Radia Sabita; Ahmad Mardalis (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to investigate the impact of celebrity endorsement, halal labels, and Word of Mouth on the purchasing intention of skincare products among millennials.Method — This study employs a quantitative research methodology, utilizing non-probability purposive sampling technique to select a sample of 200 millennial respondents who have used Safi skincare products. The data collection method involves the use of a questionnaire distributed through Google Forms, which consists of primary data collected directly from the respondents. The research data is analyzed using outer model analysis and inner model, as part of the data processing procedures.Result — The study findings indicate an insignificant effect of celebrity endorsement and halal labels on the purchasing intention of skincare products among millennials, whereas the influence of Word of Mouth on purchasing intention is positively and significantly supported.Contribution — This study provides new and important insights into the preferences and behavior of millennial consumers in the skincare market.